Epistemology of the Integration of Religion and Science Qur'anic Perspective - Aziz, Husein (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2022)
The problem facing contemporary epistemology is the dichotomy between revelation, reason, and the senses. The West prioritizes reason and senses, ignoring revelation, causing civilization to deviate from its nature. Eastern Islam puts forward revelation that ignores reason and senses so that it cannot solve contemporary problems because its knowledge is not built on natural and social laws. This paper is intended to answer this epistemological problem by using a philosophical method with a library research approach. From this discussion, it was found that there are three tools for producing knowledge according to the perspective of the Qur'an, namely, revelation, reason, and the senses. Revelation is a tool to know the unseen while reason and senses are tools to produce natural and social domains. All of these tools are combined and integrated into obtaining the expected knowledge.